2020
DOI: 10.3389/fvets.2020.569739
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Non-Invasive Vagus Nerve Stimulation (gammaCore VET™) for the Treatment of Refractory Seizure Activity in Dogs

Abstract: Idiopathic epilepsy is the most common chronic neurologic condition in dogs. Approximately 20-30% of those dogs are refractory to standard medical therapy and commonly experience side effects from antiepileptic drugs. Non-invasive vagus nerve stimulation (nVNS) has been frequently used in human medicine as an adjunct seizure therapy with low incidence of adverse events. Canine studies are limited to invasive surgical implants with no non-invasive evaluations currently published. We investigated the feasibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…Previous VNS clinical trials in veterinary medicine did not use the VNS external magnet ( 5 , 6 ). The termination of seizure activity and shortening of seizure durations and severity using a magnet-induced stimulation have been reported in humans ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous VNS clinical trials in veterinary medicine did not use the VNS external magnet ( 5 , 6 ). The termination of seizure activity and shortening of seizure durations and severity using a magnet-induced stimulation have been reported in humans ( 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…A long-term follow-up study on epilepsy patients for whom VNS parameters were gradually adjusted reported gradual reductions in median seizure frequency of 25, 40, and 53% after 3, 6, and 12 months of VNS, respectively ( 4 ). In veterinary medicine, two clinical studies on surgically implantable VNS and transcutaneous non-invasive VNS indicated the potential of VNS as adjunctive therapy for dogs with DRE ( 5 , 6 ); mean reductions in seizure frequency of 34.4% and 25.9% were reported after 13 and 16 weeks of VNS, respectively. However, the long-term efficacy and safety of VNS in dogs and adjustments of VNS stimulus dosing remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Cervical, non-invasive VNS (nVNS) devices, such as GammaCore (NJ, USA), are designed primarily to stimulate myelinated sensory afferent vagus nerve fibers as they ascend through the neck in the carotid sheath, using a battery-powered external electrical stimulator. This device has been approved and is being prescribed in several countries mainly for the treatment of primary headache and is CE marked in the EU for the treatment of primary headache, epilepsy, bronchoconstriction, anxiety, depression, and gastric motility disorders (Mwamburi et al 2017 ; Robinson et al 2020 ). More recently, this device was also tested in a short-term proof-of-concept study for patients with treatment-refractory gastroparesis, as an alternative for implantable gastric electric stimulation devices (Paulon et al 2017 ).…”
Section: Strategies For Precision Vagus Neuromodulationmentioning
confidence: 99%
“…Despite the favorable response observed in some dogs, the cost, unreliable functionality and short- and long-term complications make a surgically implanted device inaccessible for many drug-resistant patients ( 10 , 11 ). The tcVNS apparatus in dogs with drug resistant idiopathic epilepsy is reported to be well-tolerated; although no significant effect on the overall reported seizure frequency was found ( 12 ). Objective measures of tcVNS effects on vagus nerve activity remain to be described.…”
Section: Introductionmentioning
confidence: 99%